2011
DOI: 10.1177/0894486511430329
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Family Business Outcomes

Abstract: To promote theoretical development in family business research, this research identified 327 dependent/outcome variables used in 257 empirical family business studies in 1998-2009. In four studies, the authors categorized outcome variables, developed a numerical taxonomy with seven clusters (performance, strategy, social and economic impact, governance, succession, family business roles, and family dynamics) plotted along two dimensions (business–family and short-term–long-term), validated their research, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(48 citation statements)
references
References 74 publications
0
44
0
4
Order By: Relevance
“…This description is based on the family business definitions of other South African authors (Van Der Merwe 2010;Visser and Chiloane-Tsoka 2014), whereas the employee numbers criteria was based on the National Small Business Amendment Act 23 of 2003 criteria (Bosch, Tait and Venter 2011). Family SMEs were specifically chosen as the focus of this study because of their contributions to the economies of countries (Family Firm Institute 2015;Yu et al 2012), including developing countries such as South Africa.…”
Section: Introduction Problem Statement and Primary Objectivementioning
confidence: 99%
“…This description is based on the family business definitions of other South African authors (Van Der Merwe 2010;Visser and Chiloane-Tsoka 2014), whereas the employee numbers criteria was based on the National Small Business Amendment Act 23 of 2003 criteria (Bosch, Tait and Venter 2011). Family SMEs were specifically chosen as the focus of this study because of their contributions to the economies of countries (Family Firm Institute 2015;Yu et al 2012), including developing countries such as South Africa.…”
Section: Introduction Problem Statement and Primary Objectivementioning
confidence: 99%
“…The literature on family-owned enterprises has traditionally been concerned with deepening our understanding of the succession stage (Bird et al, 2002;Benavides et al, 2011;Yu et al, 2012). This has been confirmed by Benavides et al (2011), who analyzed 684 research papers and identified that succession is the most widely studied topic, with 123 of them.…”
Section: Introductionmentioning
confidence: 69%
“…This situation can mainly be explained by the recognition that the succession stage is one of the most critical issues in the continuity of the family business. Nonetheless, the study of succession has focused on the characteristics of its process, the influence of succession plans, some of the transitions tool, the relevance of management training and development or the impact of compensation schemes (Yu et al, 2012). However, little attention has been given to issues related to viables options to perennate the family business.…”
Section: Introductionmentioning
confidence: 99%
“…As Van Buuren (2007) attests, approximately 80% of all businesses in South Africa have family ownership and about 60% of all the listed companies on the Johannesburg Stock Exchange (JSE) had some family involvement, at least during their start-up phase. Williams et al (2013) concur that family businesses are unique and influential in the business sphere and many agree that what makes these enterprises unique is the interaction of the family with business (Yu, Lumpkin, Sorenson & Brigham, 2012).…”
Section: Importance and Uniqueness Of Family-owned Businessesmentioning
confidence: 99%